“We will not atikuloot our future!”: Nigerianness as stance-taking in online political discussion forums - Ugah, Helen Ufuoma (Linguistik Online, 2023)
This study argues that stance-taking, a discourse strategy in linguistics, serves the purpose of giving citizens voices to engage politicians on different social media platforms and taking them to task on their political agendas during electioneering campaigns. It aims to evince the extent to which Nigerians utilise Nigerianness – the domestication and acculturation of English language, to express their stances about the various socio-political realities in Nigeria. It deploys online comments generated from 20 posts in Nairaland and Sahara Reporters about the Nigerian 2019 general elections, and applies Martin/White’s (2005) Appraisal Theory to address Nigerians’ functional use of Nigerianness to embody their perceptions of the Nigerian socio-political dynamics.The study evinces that online forums are public spaces that enable Nigerians to follow up on and participate in debates on political events in the country, and the use of Nigerianness gives insight into the expectations of Nigerians from their political leaders.